2005
DOI: 10.1073/pnas.0505835102
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a Bacillus subtilis mobile genetic element by intercellular signaling and the global DNA damage response

Abstract: Horizontal gene transfer contributes to the evolution of bacterial species. Mobile genetic elements play an important role in horizontal gene transfer, and characterization of the regulation of these elements should provide insight into conditions that influence bacterial evolution. We characterized a mobile genetic element, ICEBs1, in the Gram-positive bacterium Bacillus subtilis and found that it is a functional integrative and conjugative element (ICE) capable of transferring to Bacillus and Listeria specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
528
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(548 citation statements)
references
References 47 publications
18
528
2
Order By: Relevance
“…CwlT has a putative signal peptide (from aa 1 to 22, black box), an SLT domain (from aa 62 to 164, light gray box) (actually this domain is a muramidase domain), and an NlpC/P60 domain (from aa 216 to 328, dark gray box). Although yddFGIJ and cwlT were previously predicted as prophage genes (22), they are now genes in ICE (23). The arrow indicates a putative terminator (Ϫ23.7 kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CwlT has a putative signal peptide (from aa 1 to 22, black box), an SLT domain (from aa 62 to 164, light gray box) (actually this domain is a muramidase domain), and an NlpC/P60 domain (from aa 216 to 328, dark gray box). Although yddFGIJ and cwlT were previously predicted as prophage genes (22), they are now genes in ICE (23). The arrow indicates a putative terminator (Ϫ23.7 kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
“…However, this region was recently determined to be an integrative and conjugative element, ICEBs1 (23). Tn916 is the best characterized ICE (35), and orf14 in it comprising 333 amino acid residues (36) exhibits very high sequence similarity with the entire region of CwlT (43% identity; from 13 aa to 329).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However it is possible that such elements could help the transfer process of the ICEs acting as triggers for the activation of the damage-repair machinery found in the host cells. It has already been suggested that the damage-repair machinery is important for the integration of the ICEs in the chromosome of the host cells (Auchtung et al, 2005).…”
Section: General Characteristicsmentioning
confidence: 99%
“…ICEBs1 has a phage-like tyrosine recombinase and excises at a higher rate upon DNA damage and in a recA-dependent manner (23). To determine if DNA damage induces the excision of ICE6013, strains JE2 and RN4220 were UV irradiated at 25 J/m 2 and 100 J/m 2 .…”
Section: Resultsmentioning
confidence: 99%